SILVER RECYCLING FROM PHOTO-PROCESSING WASTE USING ELECTRODEPOSITION METHOD - Mochammad Feri Hadiyanto; Agus Kuncaka (Indonesian Journal of Chemistry, 2002)
Silver electrodeposition of photo-processing waste and without addition of KCN 1,0 M has been studied for silver recycling. Photo procesing waste containing silver in form of [Ag(S2O3)2]3- was electrolysed at constant potential and faradic efficiency was determined at various of electrolysis times. Electrolysis of 100 mL photo processing waste without addition of KCN 1,0 M was carried out at constant potential 1.20 Volt, while electrolysis 100 mL photo procesing waste with addition of 10 mL KCN 1,0 M electrolysis was done at 1.30 Volt.The results showed that for silver electrodeposition from photo processing waste with addition of KCN 1,0 M was more favorable with faradic efficiency respectively were 93,16; 87,02; 74,74 and 78,35% for 30; 60; 90 and 120 minutes of electrolysis.